Holocaust, genocide, and the law : a quest for justice in a post-holocaust world - Bazyler, Michael J. (New York, NY : Oxford University Press, 2016)
This work examines the background of the Holocaust and genocide through the prism of the law; the criminal and civil prosecution of the Nazis and their collaborators for Holocaust-era crimes; and contemporary attempts to criminally prosecute perpetrators for the crime of genocide. It provides the history of the Holocaust as a legal event, and sets out how genocide has become known as the 'crime of crimes' under both international law and in popular discourse.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 31, 2016).
Keywords: Genocide (International law); International criminal law; Holocaust, Jewish (1939-1945) -- Influence; World War, 1939-1945 -- Law and legislation; Law